TENUICOLLOSIS IN SLAUGHTERED SHEEP AT DUHOK ABATTOIR- KURDISTAN REGION OF IRAQ - Nacheervan.M.Ghaffar (Basrah Journal of Veterinary Research)
A study on the prevalence and monthly incidence of Cysticercus tenuicollis metacestodes of sheep were carried out in Duhok abattoir(north of Iraq) .The work was conducted during the period from October.2008- to September.2009 by weekly regular visits to the slaughterhouse. All slaughtered animals were apparently healthy, were of local breed, of both sexes originated from some areas with non –descriptive features. Visual inspection of the lesion and traditional procedure were followed.Age,sex and different locations of cysts were widely investigated in each species and then tabulated . Out of 4716 sheep examined, only 31(0.7%) of sheep had cysts, with absence of these cysts in both goats and cattle. However, the vesicles were only present in female sheep. The highest infection rate was found in sheep older than 2 years(1.7%),while the lowest was in sheep younger than one year(0.1%).The heaviest incidence was observed in Febrewery,2009(1.4%)and the lowest was in Jun and July(0.3%). The commonest locations of the cysts were in the mesentery (29%) followed by the uterus (16%) with few cases in other visceral organs.